Perception and Appreciation of The Indonesian Plural Society Toward Cultural Diversity - Suryatni, Luh; Widana, I Dewa Ketut Kerta (Technium Social Sciences Journal, 2023)
The perception and appreciation of Indonesia's pluralistic society towards cultural diversity is inseparable from intercultural synergies based on enculturation and acculturation within the framework of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The purpose of this writing is to study and understand the importance of perceptions and appreciation of Indonesia's pluralistic society towards cultural diversity. This study uses a descriptive literature review by selection of information sources through books, journals as well as laws and regulations related to the problem. The results show that perceptions and appreciation of Indonesia's plural society can build a spirit of unity in cultural diversity